29‐3: Floating Image for Ultrahigh Resolution Display Device Using Integral Photography Theory. Issue 1 (May 2017) - Niu, Lei; Li, Jialing; Liu, Yaoyang; Lu, Feng; Ma, Jun; Gao, Yulong
Abstract : We proposed a novel floating images display with an advanced light field system. The viewing angle was improved owing to the increased space between the adjacent lenses. Moreover, the ghost image problem in the integral image system has been solved by employing the novel unit image arrangement. A prototype of the floating image display has been achieved with perfect view‐angle feature, ultra‐high resolution and dynamic effect.